Observations of slip patterns on the surface of fatigued gold using the scanning tunnelling microscope - Grosskreutz, J.C.; Bowles, C.Q.; Wahab, A.A. (Springer Netherlands, 1992)
Observations of fatigue-induced slip patterns on the surface of polycrystalline gold (+99.9%) using the scanning tunnelling microscope (STM) are presented. The samples were cycled in four-point bending between zero and 0.0025 strain for 250 and 2500 cycles. STM observations of the sample fatigued for 250 cycles revealed broad slip bands 0.38–0.69 m wide containing narrow slip bands 0.015–0.123 m wide and fine slip lines 0.006 m wide. The depth of these features are 20–57 nm for broad slip bands, 3–7 nm for narrow slip bands, and approximately 2–4 nm for fine slip lines. The sample fatigued for 2500 cycles showed similar values for the width of the slip bands and slip lines except that their depth was increased by a factor of between 2 and 4 times for the narrow slip bands and the fine slip lines. Apparent persistent slip bands (PSBs) spaced 2.4 m, 300–500 nm deep were also observed. These results demonstrate that STM is a significant new tool for observing and distinguishing various types of fatigue-induced surface slip patterns on suitably prepared samples. The vertical resolution obtained with STM is vastly superior to current SEM and TEM methods.